Successive Extraction of Glycyrrhizic Acid and Liquiritin from Licorice with Cellulase and Pectinase - Ge, Xizhen; Lin, Qiang; Gu, Chunxiu; Zhu, Yan; Jiang, Nan; Zhao, Bingbing; Wang, Meng; Tian, Pingfang (Asian Journal of Chemistry, 2012)
A simple and environment amicable method for successive extraction of glycyrrhizic acid (GA) and liquiritin from licorice root was developed using cellulase and pectinase for pretreatment (licorice root: cellulose: pectinase = 650:2:1, pH 5.0-6.0, 50 ºC, 160-180 min). 10 % ammonia as a solvent was verified to be more effective than 10 % ethanol for extracting glycyrrhizic acid from licorice based on pretreatment with pectinase and cellulose, resulting in 45.61 % of glycyrrhizic acid purity. Subsequently, 10 and 60 % of aqueous ethanol solution were recruited to successively elute glycyrrhizic acid from the enzyme-digested extracts in D101 macroporous adsorption resin (MAR) and the glycyrrhizic acid purity was increased to 86.33 %. After extraction of glycyrrhizic acid, the residue of licorice root was treated with the above two kinds of enzymes, extracted with 90 % ethanol, 0.32 % of liquiritin purity was achieved. Eluted by macroporous adsorption resin AB-8, the purity of liquiritin was up to 2.78 %. Purified by polyamide, the purity was elevated to 10.89 %. Compared with previous protocols, this method is benign to the environment and the employed enzymes and macroporous resin are suitable for large-scale separation of glycyrrhizic acid and liquiritin from licorice root successively.